The Potential of Sleeping Medicine Plants in Overcoming Insomnia - Hakim, Ali Rakhman; Nisrina, Salwa; Asi, Seva Bela N.; Sarah, Siti; Gresia, Sola; Wulandari, Suci Sri (Universitas Ibn Khaldun Bogor, 2024)
Insomnia is a common health problem that interferes with quality of life. This study examines the potential of a combination of herbal ingredients in overcoming insomnia, including Valerianae Radix, Myristicae Semen, Eleuthroginseng Radix, and Polygalae Radix. Each ingredient has active components that contribute to its pharmacological effects. The results of the study show that this combination can be an effective and safe alternative to the treatment of insomnia.